Death of Leukemia Cells and Platelets Induced by 3,3′-Dihydroxy-4,5-Dimethoxybibenzyl Is Mediated by p38 Mitogen-Activated Protein Kinase Pathway - Natalia Rukoyatkina; Tatyana Sokolova; Nikita Pronin; Andrei Whaley; Anastasiia O. Whaley; Stepan Gambaryan (Molecules, 2025)
Bibenzyls are now recognized as compounds for use in cancer therapy, and many molecules from the bibenzyl group have shown promising anticancer activity; therefore, the characterization of new bibenzyls with strong biological activity is important for developing new anticancer drugs. In this study, we compared the effects of three bibenzyls (3,3′-dihydroxy-4,5-dimethoxybibenzyl, 3,5-dihydroxy-4-methoxybibenzyl and 3,5,3′-trihydroxy-4-methoxybibenzyl) isolated from Empetrum nigrum and erianin on platelets and the MOLT-3 T-lymphoblast cell line. Among the studied bibenzyls, 3,3′-dihydroxy-4,5-dimethoxybibenzyl significantly reduced the viability of MOLT-3 cells and platelets and induced strong phosphatidylserine (PS) surface exposure. We showed that 3,3′-dihydroxy-4,5-dimethoxybibenzyl induced the death of MOLT-3 cells and platelets, which was not mediated by apoptosis, pyroptosis, necroptosis, autophagy, or calpain-dependent pathways, and that the p38 MAP kinase pathways are at least partly involved in the activity of 3,3′-dihydroxy-4,5-dimethoxybibenzyl. In conclusion, our data show that 3,3′-dihydroxy-4,5-dimethoxybibenzyl could be a promising candidate for future analysis as an anticancer drug.